Understanding the South : how northern donor agencies and NGOs understand the needs and problems of Southern NGO clients - Ahmad, Mokbul Morshed (Dhaka : Maniruddin Ahmed, 2001)
With reference to NGOs in Bangladesh and Ireland.
Includes bibliographical references and index.
Keywords: Non-governmental organizations -- Bangladesh; Community development -- Bangladesh; Non-governmental organizations -- Ireland; Economic assistance, Irish -- Bangladesh